Impact of age on breast cancer mortality and competing causes of death at 10 years follow-up in the adjuvant TEAM trial. (August 2018) - Derks, M.G.M.; Bastiaannet, E.; van de Water, W.; de Glas, N.A.; Seynaeve, C.; Putter, H.; Nortier, J.W.R.; Rea, D.; Hasenburg, A.; Markopoulos, C.; Dirix, L.Y.; Portielje, J.E.A.; et al.
Abstract: Aim: Due to increasing life expectancy, patients with breast cancer remain at risk of dying due to breast cancer over a long time. This study aims to assess the impact of age on breast cancer mortality and other cause mortality 10 years after diagnosis. Methods: Postmenopausal patients with hormone-receptor positive breast cancer were included in the Tamoxifen and Exemestane Adjuvant Multinational (TEAM) trial between 2001 and 2006. Age at diagnosis was categorised as <65 years (n = 3369), 65–74 years (n = 1896) and ≥75 years (n = 854). Breast cancer mortality was assessed considering other cause mortality as competing event using competing risk analysis. Results: After a median follow-up of 9.8 years (interquartile range 8.0–10.3), cumulative incidence of breast cancer mortality increased with increasing age (age <65 years, 11.7% [95% confidence interval CI: 10.2–13.2]; 65–74 years, 12.7% (11.2–14.2) and ≥75 years, 15.6% (13.1–18.0)). Univariate subdistribution hazard ratio (sHR) increased with increasing age (age: 65–74 years, sHR: 1.08, 95% CI: 0.92–1.27 and ≥75 years sHR: 1.30, 95% CI: 1.06–1.58, P = 0.013). Multivariable sHR adjusted for tumour and treatment characteristics increased with age but did not reach significance (age 65–74 years, sHR: 1.11, 95% CI: 0.94–1.31; ≥75 years, sHR: 1.18, 95% CI: 0.94–1.48, P = 0.055). Conclusion: Ten years after diagnosis, older age at diagnosis is associated with increasing breast cancer mortality in univariate analysis, but it did not reach significance in multivariable analysis. This is not outweighed by a substantially higher other cause mortality with older age. This underlines the need to improve the balance between undertreatment and overtreatment in older patients with breast cancer. The trial was registered in International Trial Databases (ClinicalTrials.gov NCT00279448, NCT00032136, andNCT00036270 ; the Netherlands Trial Registry NTR267). Highlights: With increasing life expectancy, there is a longer period to die due to breast cancer. Breast cancer mortality increased with age despite higher competing mortality. Even at older age, breast cancer remains an important cause of death. Older patients are at risk of both undertreatment and overtreatment. Clinicians should aim to accurately balance harms and benefits of treatment in elderly.